Reforming Fiqh Al-Bi’ah (Ecological Jurisprudence) based on Islam Hadhari: An Integration Conservation Framework of Muamalah and Culture - Amiruddin, Muhammad Majdy; Haq, Islamul; Anwar, Haerul; Haris, Asmaddy (NAJAHA, 2024)
This study seeks to reconstitute Fiqh al-Bi’ah through the Islam Hadhari framework, amalgamating Muamalah and cultural aspects into a holistic ecological management model. The research employed a grounded theory methodology in Terengganu, Malaysia, utilizing data collection methods that included in-depth interviews with local community members and participatory observations of marine conservation practices. The gathered data were subjected to thematic analysis to discern patterns and correlate them with Islamic ecological principles. Data validation was accomplished via triangulation, guaranteeing consistency across many sources and methodologies. The results indicate that local traditions, including mangrove conservation, sustainable fishing methods, and spiritual ceremonies, correspond with the tenets of tawazun (balance), adl (justice), and ri’ayah al-bi’ah (environmental stewardship). This reformulation presents new dimensions, including Muwafaqah Ruhiyah Ma’a al-Tabi’ah (spiritual harmony with nature) denoting the religious aspect, Istimrariyah Bayn al-Ajyal (intergenerational sustainability) emphasizing economic sustainability across generations, and Taqdir al-Iqtisad al-Mahalli (empowerment of local economies), which illustrates the amalgamation of cultural heritage and economic resilience in ecological management. This approach's primary strength is its amalgamation of Islamic ideals with pragmatic conservation measures, promoting a balance between environmental sustainability and community welfare. Nonetheless, the study's restricted geographic emphasis on Terengganu poses a hurdle for generalizing its application to broader contexts. Subsequent studies should extend this model to more regions characterized by varied ecological and cultural contexts, affirming its universal applicability. This study significantly contributes to Islamic environmental discourse by presenting a reproducible methodology for tackling global ecological concerns through a value-oriented approach.